Razoes para o desenvolvimento do método experimental na Ciência Política contemporânea - Almeida, Sabrina Karlla Oliveira de (2016)
With the advent of the twentieth century, technological advance and the development in various areas of knowledge led to some changes in the design of the study of science. In the current paradigm, there is a constant commitment in the political science with the issue of causal inference. The experimental method has clear ability to claim causal relationships between variables of interest. Thus, it presents as a pragmatic method for improving theories. We will examine, in this study, the reasons that have motivated growing interest by researchers in the methodology